Bimbingan Guru Sekolah Minggu Dalam Menangani Attention Deficit Hyperactivity Disorder (ADHD) Pada Anak Sekolah Minggu - Ratni Mbuik (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2025)
Sunday school is an activity that is carried out every Sunday, Sunday school is carried out in order to foster, educate and become a bridge for children to be able to meet God or be able to know God through the truth conveyed. Sunday school children are children who must be instilled with the truth through Sunday school teachers, therefore the school teacher must be a role model or be an example and live God in himself, so that when teaching, children will receive the spirit that the teacher has. The method used in this research is qualitative through literature review collected through books, journals and articles to get very accurate data. With the aim of being able to help find solutions in dealing with ADHD children in Sunday school. Children who experience ADHD are not a disease, so as parents must know what the child is experiencing, and as parents must provide early treatment such as taking the child to a psychologist / therapist so that the child gets treatment before it is too late.